Pengembangan Mouth Nanospray Minyak Atsiri Biji Jintan Hitam (Nigella sativa L.) : Sifat Fisik, Stabilitas, dan Aktivitas Antibakteri - Rahayu, Milda; Hariyani, Septi; Lestari, Uce (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2026)
Halitosis is one of the oral health problems that is quite high in prevalence and can reduce the quality of life of sufferers. This study aims to formulate and evaluate the physical quality, characteristics of nanoparticles, and antibacterial activity of mouth nano spray containing black cumin essential oil (Nigella sativa L.). The formulation is made in four variations of essential oil concentration (F1 0.25%; F2 0.5%; F3 1%; F4 1.5%) using the nanoemulsion method. Physical quality evaluation included organoleptic, pH, homogeneity, and viscosity tests, while nanoparticle characterization was carried out using a Particle Size Analyzer (PSA). Antibacterial activity was tested against Streptococcus mutans using disc diffusion method. The results show that all formulas have good physical properties with a liquid, clear, and homogeneous form. The pH value is in the range of 6–6.7 which corresponds to the pH of the mouth. The PSA test on F3 yielded a particle size of 42.7 nm with a PDI of 0.6, but a potential zeta value of –5.6 μV indicated low electrostatic stability. The antibacterial activity test showed that F2, F3, and F4 had strong inhibition with inhibition zone diameters of 11.78 mm, 11.57 mm, and 13.10 mm, respectively, higher than positive controls (8.39 mm). Based on these results, the F4 formula with a concentration of 1.5% provides the most optimal antibacterial activity.